The. Women. The Subject(s) of The Unnatural and Accidental Women and Unnatural and Accidental - Wunker, Erin (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
This article has a methodological framework that uses post structural theories of the archive as well as performance theory to compare Marie Clements’s play The Unnatural and Accidental Women with Carl Bessai’s celluloid adaptation Unnatural and Accidental. The article opens with a claim that Clements’s play incites a radical recognition of the Other through a Derridan politics of "hauntology." The article then suggests that while Clements’s play leads the audience in a performative and ethical recognition of the Other, the celluloid adaptation destabilizes the radical politics of the play. The article closes with a consideration of what is lost in Bessai’s adaptation that cuts from its title the very subjects of Clements’s play: the women. Résumé Cet article propose un cadre méthodologique qui s’appuie sur des théories poststructurelles de l’archive de même que sur la théorie du jeu, lesquelles sont appliquées à la pièce The Unnatural and Accidental Women de Marie Clements et à l’adaptation cinématographique Unnatural and Accidental de Carl Bessai. L’auteure avance d’abord que la pièce de Clements incite à une reconnaissance radicale de l’Autre par une politique derridienne de la «.hantologie.». Il poursuit en faisant valoir que, si la pièce de Clements mène son public vers une reconnaissance performative et éthique de l’Autre, l’adaptation cinématographique déstabilise la politique radicale mise de l’avant dans la pièce. L’article conclut par un examen de ce qui est perdu dans l’adaptation de Bessai, qui retranche de son titre le sujet même de la pièce de Clements: les femmes.